(untitled) (Texas Journal of Philology, Culture and History, 2024)
The history of nations, way of living, ceremonies, rites and traditions can be studied not only by ancient remains or material monuments, like archeology does, but also with the assistance of language. Language does not exist without culture, just as culture does not exist without language. The cultural linguistic studies the problems of interaction between language and culture. The basic unit of the description in linguistic and cultural studies is linguocultural. This article makes an attempt to describe and emphasize the complexity of the structure and functioning of the linguocultural. A working hypothesis is to put forward that linguocultural as an integrated unit, able to determine the correlation between culture and language in linguistic and cultural studies